2020
DOI: 10.1101/2020.04.29.20076570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Negative impact of hyperglycemia on Tocilizumab therapy in COVID-19 patients

Abstract: Tocilizumab is used for treating moderate-severe Covid-19 pneumonia by targeting IL-6 receptors (IL-6R) and reducing cytokine release, but the pooled rate ratio among diabetic patients with adverse vs those with the more favorable course was 2.26. To date, the hyperglycemia has been shown to increase IL-6 and IL-6R, which has been suggested as a severity predictor in lung diseases of Covid-19 patients. However, there are no data about the effects of tocilizumab therapy on outcomes of hyperglycemic Covid-19 pat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…TCZ also has inevitable limitations and clinical defects in the treatment of COVID-19. For example, Optimal COVID-19 infection management with TCZ is not achieved during hyperglycaemia in both diabetic and non-diabetic patients that TCZ administration neither decreases IL-6 levels nor attenuates risk of severe outcomes (55). Similarly, the use of TCZ fails to decrease the mortality rate at 30 days of patients with severe COVID-19 acute respiratory distress syndrome with hyperinflammation, after correction for pre-existing comorbidities and the need for respiratory support (56).…”
Section: Discussionmentioning
confidence: 99%
“…TCZ also has inevitable limitations and clinical defects in the treatment of COVID-19. For example, Optimal COVID-19 infection management with TCZ is not achieved during hyperglycaemia in both diabetic and non-diabetic patients that TCZ administration neither decreases IL-6 levels nor attenuates risk of severe outcomes (55). Similarly, the use of TCZ fails to decrease the mortality rate at 30 days of patients with severe COVID-19 acute respiratory distress syndrome with hyperinflammation, after correction for pre-existing comorbidities and the need for respiratory support (56).…”
Section: Discussionmentioning
confidence: 99%
“…As such, tocilizumab has been proposed as a therapeutic option for compassionate use in patients with COVID-19 [66]. A recent observation has found that hyperglycaemia, both at admission and during the hospital stay, was associated with higher IL-6 levels and a reduced efficacy of tocilizumab, leading to poorer outcomes in COVID-19 patients regardless of the presence or not of known diabetes [67]. However, further studies are now necessary to confirm this finding.…”
Section: Role Of Obesitymentioning
confidence: 99%
“…Severe adverse drug reactions related to TCZ were noted in 11 (59%) patients; infections (as a complication of the main disease) were reported in 13 (6.3%) patients. According to Marfella et al [ 65 ], during treatment with TCZ in COVID-19 patients, hyperglycemia is associated with higher risk as compared to the patients with normal blood glucose levels (P < 0.009).…”
Section: Efficacy Of Anti-il-6r and Anti-il-6 Monoclonal Antibodies Imentioning
confidence: 99%